Ethics and Language Assessment Standards in Sociocultural-Historical Contexts: A Systematic Review - Thaweesak Chanpradit; Erikson Saragih (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2026)
Ethics and language assessment standards ensure assessors’ fairness, accountability, and transparency. However, these can be questionable in different sociocultural historical contexts. This review seeks an understanding of how ethics and standards intersect with cultural-historical factors in language assessment, including how assessor bias could be minimized in different cultural-historical contexts. Herein, the review examines research articles on ethical considerations in assessment standards, cultural responsiveness, historical developments, impacts on assessment outcomes, and challenges and solutions. Using the PRISMA procedure with citation chaining, 40 peer-reviewed articles were identified and included in the review. The findings revealed the rise of justice-oriented and culturally sustaining ethical frameworks that enhance fairness in language assessment but remain difficult to fully implement in actual ELT practices. Cultural responsiveness tends to be restricted by standardization, institutional constraints, and colonial legacies that continue to shape assessment ethics. However, when applied in an effective manner, ethical standards could improve fairness and stakeholder trust, yet systemic inequities, limited resources, and emerging issues from AI integration would pose ongoing challenges. Therefore, policymakers, educators, and test developers should stress the need for collaborative, context-sensitive, and reflective approaches that further promote culturally grounded, socially just, and technologically informed ethical practices in language assessment.